Learning-to-export Effect as a Response to Export Opportunities: Micro-evidence from Korean Manufacturing - Chin Hee Hahn; Yong-Seok Choi (KDI Journal of Economic Policy, 2021)
This paper aims to investigate whether there is empirical evidence supporting the learning-to-export hypothesis, which has received little attention in the literature. By taking full advantage of plant-product level data from Korea during 1990-1998, we find some evidence for the learning-to-export effect, especially for the innovated product varieties with delayed exporters: their productivity, together with research and development and investment activity, was superior to their matched sample. On the other hand, this learning-to-export effect was not significantly pronounced for industries protected by import tariffs. Thus, our empirical findings suggest that it would be desirable to implement certain policy tools to promote the learning-to-export effect, whereas tariff protection is not justifiable for that purpose.
Keywords: F13; F14; 330; Learning-to-export; Difference-in-differences; Matching